Reproducción vegetativa de dos especies arbóreas en un manglar de la costa norte del Pacífico mexicano - Benítez Pardo, Daniel; Flores Verdugo, Francisco; Valdez Hernández, Juan Ignacio (Instituto de Ecología, A.C., 2016)
The obtention of new saplings through the induction of root formation in aerial shoots and conventional cuttings is a first, important step for agronomic management of mangrove forests. This possibility was studied with the species Laguncularia racemosa and Conocarpus erectus, with experiments carried out during four periods of the year, corresponding to the conventional four seasons of temperate climates. Root formation of aerial shoots on a substrate of ground coconut burlap and sawdust was 90% successful during summer (wet season). Conventional cuttings of young (soft) and older (semi-hard) wood were less successful. Only 50% and 30% of the semi-hard and soft cuttings of L. racemosa had rooted at the end of the trials. Those of C. erectus had few leaves and buds, which lasted between 6 and 12 months, but were unable to generate a functional root system.